THE STUDENTS WORKSHEET DEVELOPMENT ON FUNGI BASED ON THE PLUS KWL’S STRATEGY TO TRAIN THE METACOGNITIVE SKILLS - Andarwati, Indrie Dwi; Susantini, Endang; Basri, Ahmad (Universitas Negeri Surabaya, 2019)
The objective of this research was to produce worksheet of fungi material based on Plus KWL?s strategy to train the metacognitive skills seen at the effectiveness. The type of this research was a development with a 3D research design that was shortened into define, design and development. The subjects of this study were students of class X MIA 1. Instruments used in this study was test. Based on the effectiveness of worksheet based on Plus KWL?s strategy was obtained from pre and posttest result which have been tested from the positive value sensitivity. This worksheet can be used to train the metacognitive skills by very good criteria that were determining the level of confidence and score. It can be concluded that the worksheet based Plus KWL ?s is very effective to train metacognitive skills